Barriers to smart waste management for a circular economy in China. (10th December 2019) - Zhang, Abraham; Venkatesh, V.G.; Liu, Yang; Wan, Ming; Qu, Ting; Huisingh, Donald
Abstract: Waste management requires a new vision and drastic improvements for a transition to a zero-waste circular economy. In reality, however, many economies are producing more and more waste, which poses a serious challenge to environmental sustainability. The problem is enormously complex as it involves a variety of stakeholders, demands behavioral changes, and requires a complete rethinking of the current waste management systems and the dominant linear economic model. Smart enabling technologies can aid in a transformation of waste management toward a circular economy, but many barriers persist. This study first shortlists twelve important barriers to smart waste management in China based on interviews with experienced practitioners. It then prioritizes these barriers through a scientific prioritization technique, fuzzy Decision-Making Trial and Evaluation Laboratory (DEMATEL), based on the survey data from three representative stakeholders. It identified three key causal barriers: the lack of regulatory pressures, the lack of environmental education and culture of environmental protection, and the lack of market pressures and demands. Practical and theoretical implications were discussed based on the research results and findings. Highlights: Waste management needs to be smarter for a zero-waste circular economy vision. Key barriers to smart waste management in China: Lack of regulatory pressures. Lack of environmental education and culture of environmental protection. Lack of knowledge of smart waste management and lack of market pressures and demands. The government must gear up regulatory pressures and environmental education.